Efektivitas Keadilan Restoratif Dalam Penyelesaian Perceraian Akibat Kekerasan Dalam Rumah Tangga Di Pengadilan Agama Stabat - M. Irvan Syahputra; Azhar (Journal Smart Law, 2025)
This study examines the application and effectiveness of the restorative justice approach in resolving divorce cases due to Domestic Violence (KDRT) in the Stabat Religious Court. The problem of the research departs from the still dominant formalistic legal approach that tends to be oriented towards the termination of legal relations, without providing optimal recovery for victims of domestic violence. This study aims to analyze the form of restorative justice implementation, assess its effectiveness, and identify normative, structural, and cultural barriers in its implementation. The research method used is field research with a qualitative approach. Data were obtained through observation of the mediation process, case documentation studies, and in-depth interviews with mediator judges, judicial officials, religious leaders, and parties to the case. The results of the study show that the restorative justice approach in the Stabat Religious Court is applied through a mediation mechanism that emphasizes dialogue, reconciliation, and the restoration of social relations. The effectiveness of this approach is reflected in the achievement of the restoration of the rights and dignity of the victims, changes in the attitude of the perpetrators through a spiritual approach, and conformity with the local wisdom values of the Lalat community. Although it still faces obstacles in the form of limitations in the form of special regulations and the influence of patriarchal culture, restorative justice has been proven to be able to reduce conflict and provide a sense of substantive justice for victims